Earth : [videorecording (DVD)] : the biography - Stewart, Iain S. (Distributed by BBC Worldwide Americas ; Distributed by Warner Home Video, 2008)
"Earth is an incredible, exceptional planet with an amazing life story full of cataclysmic disasters, eleventh-hour coincidences that save it from extinction, and an astonishing power to continually regenerate. This... series uses breathtaking footage and specialist imaging to tell the story of the great forces that shape the planet - volcanoes, the ocean, the atmosphere and ice. Traveling from Ethiopia's unique lava lake to an ice cave under a glacier in Greenland and a host of amazing locations in between, examine the forces that have helped create and foster life on Earth..." -Container